OPTIMASI PRODUKSI CRUDE PALM OIL (CPO) DAN INTI SAWIT (KERNEL) MENGGUNAKAN TEKNIK 2 FASE DI PT. LIL - Vera Devani; Yulia Aiza (Jurnal Teknologi, 2023)
PT. LIL is one of the companies engaged in the business of managing palm oil into Crude Palm Oil (CPO) and palm kernel oil or Palm Kernel Oil (PKO). The method used in this research is the Simplex Method which is one of the methods in the Linear Program that helps in solving a problem with more than two variables. The purpose of this study is to determine the optimal profit, type and number of products to be produced and to determine the value of sensitivity to the optimum solution achieved. Based on the results of research conducted, it can be concluded that the optimal benefits obtained by PT. LIL is Rp. 11,038.7 per kg by producing Crude Palm Oil (CPO) as much as 1.0776 kg and kernels as much as 0.9224 kg. If there is a change in the objective function coefficient for the base variable, the gain for the CPO and kernel remains optimal if it is greater than 0. If there is a change in the right side of the boundary, an optimal percentage ofcontent is oil loss CPO1.45% and kernel is 0.24%, moisture CPO 0.25% and 6.36% kernel, dirty 0.05% CPO and 6.7% kernel and FFA (Free Fatty Acid) CPO content 0%.